2021
DOI: 10.1002/chem.202101924
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Cationic Polypeptide Supramolecular Nanogels for Intracellular DNA Delivery

Abstract: Supramolecular nanogels are an emerging class of polymer nanocarriers for intracellular delivery, due to their straightforward preparation, biocompatibility, and capability to spontaneously encapsulate biologically active components such as DNA. A completely biodegradable three‐component cationic supramolecular nanogel was designed exploiting the multivalent host‐guest interaction of cyclodextrin and adamantane attached to a polypeptide backbone. While cyclodextrin was conjugated to linear poly‐L‐lysine, adama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Recently our group presented the preparation of self‐assembled cationic polypeptide supramolecular nanogels and their application for intracellular DNA delivery [51a] . Nanogels were prepared by one pot, one step self‐assembly of three component system purely based on poly‐ L– Lysine (PLL) as a backbone (see Figure 7a).…”
Section: Polymer Cyclodextrin Hydrogelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently our group presented the preparation of self‐assembled cationic polypeptide supramolecular nanogels and their application for intracellular DNA delivery [51a] . Nanogels were prepared by one pot, one step self‐assembly of three component system purely based on poly‐ L– Lysine (PLL) as a backbone (see Figure 7a).…”
Section: Polymer Cyclodextrin Hydrogelsmentioning
confidence: 99%
“… (a) Design strategy of supramolecular CD−Ad nanogel based on poly‐ L– Lysine [51a] . The nanogels were loaded with DNA and their cellular uptake and release was studied using a luciferase assay.…”
Section: Polymer Cyclodextrin Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among polymeric nanocarriers, the most exciting innovations in nanomedicine for gene delivery are nanogels, because they are biocompatible, possess high loading capacity, and have potential responsivity to environmental stimuli [ 10 , 11 ]. Recent studies have shown the promising use of synthetic nanogels as miRNA [ 12 , 13 , 14 , 15 , 16 , 17 ], siRNA [ 18 ], mRNA [ 19 ], and pDNA [ 20 ] delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…While the effectiveness of different miRNAs and their role as either oncogenes or tumor suppressors under certain conditions has been well established, many studies on synthetic smart nanogels have neglected to explicate the connection between miRNA loading capacity and release profile with different N/P ratios, either with or without the presence of biological stimuli [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], which is the main focus of this study. In the current study, we developed biodegradable reduction-sensitive nanogels for miRNA encapsulating and enhancing miRNA release in a cancer-mimicking environment where the GSH level is elevated ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%